q-Parametric Bleimann Butzer and Hahn Operators - Mahmudov, Nazim I.; Sabancıgil, Pembe (Hindawi Publishing Corporation, 2008)
We introduce a new q-parametric generalization of Bleimann, Butzer, and Hahn operators in C∗ 1x0, ∞ . We study some properties of q-BBH operators and establish the rate of convergence for q-BBH operators. We discuss Voronovskaja-type theorem and saturation of convergence for qBBH operators for arbitrary fixed 0 <q< 1. We give explicit formulas of Voronovskaja-type for the q-BBH operators for 0 <q< 1. Also, we study convergence of the derivative of q-BBH operators.
The file in this item is the publisher version (published version) of the article.
Keywords: q-parametric generalization; q-BBH operators.; Zeller operators